Matured hiPSC-derived cardiomyocytes possess dematuration plasticity - Fang Meng; Maxwell Kwok; Yen Chin Hui; Ruofan Wei; Alejandro Hidalgo-Gonzalez; Anna Walentinsson; Henrik Andersson; Frederik Adam Bjerre; Qing-Dong Wang; Ditte C. Andersen; Ellen Ngar-Yun Poon; Daniela Später; et al. (Journal of Molecular and Cellular Cardiology Plus)
Human induced Pluripotent Stem Cell-derived cardiomyocytes (hiPSC-CMs) are increasingly used to identify potential factors capable of inducing endogenous cardiomyocyte proliferation to regenerate the injured heart. L-type calcium channel blockers have previously been identified as a class of factors capable of inducing matured hiPSC-CMs to proliferate. However, the mechanism by which L-type calcium channel blockers promote hiPSC-CM proliferation remains unclear. Here we provide evidence that matured hiPSC-CMs possess plasticity to undergo dematuration in response to certain pharmacological compounds. Consistent with primary cardiomyocyte maturation during perinatal development, we found that centrosome disassembly occurs in hiPSC-CMs during plate-based, temporal, maturation. A small molecule screen identified nitrendipine, an L-type calcium channel blocker, and 1-NA-PP1, a Src kinase inhibitor, as factors capable of inducing centrosome reassembly in a subpopulation of hiPSC-CMs. Furthermore, centrosome-positive hiPSC-CMs were more likely to exhibit cell cycle activity than centrosome-negative hiPSC-CMs. In contrast, neither nitrendipine or 1-NA-PP1 induced centrosome reassembly, or cell cycle activity, in neonatal rat ventricular myocytes (NRVMs). Differential bulk transcriptome analysis indicated that matured hiPSC-CMs, but not NRVMs, treated with nitrendipine or 1-NA-PP1 undergo dematuration. ScRNA transcriptome analysis supported that matured hiPSC-CMs treated with either nitrendipine or 1-NA-PP1 undergo dematuration. Collectively, our results indicate that matured hiPSC-CMs, but not primary NRVMs, possess plasticity to undergo dematuration in response to certain pharmacological compounds such as L-type calcium channel blockers and Src-kinase inhibitors. This study shows that once mature, hiPSC-CMs may not maintain their maturity under experimental conditions which may have implications for experimental systems where the state of hiPSC-CM maturation is relevant.